INITIAT‐E.D.: Impact of timing of INITIation of Antibiotic Therapy on mortality of patients presenting to an Emergency Department with sepsis. (6th April 2015) - Wisdom, Alice; Eaton, Vaughn; Gordon, David; Daniel, Santhosh; Woodman, Richard; Phillips, Cameron
Abstract Objectives To analyse the association between time from triage to administration of initial antibiotics and mortality in all patients presenting with sepsis to a tertiary hospital ED. Methods A retrospective review of patients presenting to the ED with sepsis from January to December 2012 was conducted at Flinders Medical Centre, South Australia. Outcome measures were: time elapsed from triage to administration of initial antibiotic therapy and in‐hospital mortality. Results A total of 220 patients presented with sepsis, comprising 102 cases of uncomplicated sepsis and 118 severe sepsis. The median time to antibiotic administration was 3.5 h (interquartile range [IQR] 1.7–6.6) and in‐hospital mortality was 28.6% (95% CI 22.6–34.6%). There was no association observed between delays to antibiotics and mortality in the total patient population. When stratified by presenting severity, patients with severe sepsis demonstrated a trend towards increased mortality when delays to antibiotics exceeded 6 h from triage (HR = 2.25, 95% CI 0.91–5.59, P = 0.08) in comparison with <1 h. Significant delays to antibiotic administration occurred when initial agents were charted as a 'regular medicine' (9.4 h, IQR 5.1–16.6) in comparison with a 'once only order' (3.4 h, IQR 1.7–6.7), P < 0.001. Conclusions Early administration of antibiotics specifically in patients with severe sepsis might be beneficial. Further studies within the ED are warranted to establish the effect of delayed antibiotics in a generalised sepsis cohort.